A Research to Identify the Problem Areas Caused by Organizational and Managerial Values(Örgütsel ve Yönetsel Değerlerin Neden Olduğu Sorun Alanlarının Belirlenmesine Yönelik Bir Araştırma) - Hakan KARA (Yönetim ve Ekonomi, 2013)
In this study, on the basis of G. Hofstede and G. England’s research on organizational and managerial values, it is aimed to determine which problems arise from organizational and managerial values in the organization. Research data needed to achieve the objective come from 166 administrators with academic and administrative authority at faculties, colleges and vocational schools of a public university. In the light of the data, the logistic regression analysis was used to determine the relationship between values and the problems caused by values. According to the results obtained by modeling, which organizational and managerial values cause which problem areas is discussed.